Challenges and Resilience: Managers' perceptions of firm performance following M&As - Richard Croucher; Keith W. Glaister; Marian Rizov; Yasin Rofcanin; Geoffrey Wood (Applied Psychology: An International Review, 2020)
We study M&As, resilience and performance, identifying links between managers' perceptions of performance and resilience, using trans-national organisational-level survey evidence (N=3613) and follow up semi-structured in-depth interviews with managers involved in M&As and demerger. Drawing on the resilience and M&A literature, we identify reasons why employees in acquired firms may be less resilient in coping with the resultant changes than those of the acquirer and why this will negatively impact perceptions of performance. We explore the causes and consequences of variations in resilience and performance within firms that acquire others, and in those that have been demerged. As anticipated, we find that although managers in acquired firms tended to report worse performance than those in acquiring firms, both tended to be more positive than firms that had not taken part in an M&A at all. We draw out implications for theory and practice.
Keywords: 330; resilience; firm performance; management perceptions; mergers and acquisitions; behavioural organisational psychology